2018
DOI: 10.1002/cam4.1754
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cardiovascular disease up to 13 year after cancer diagnosis: A matched cohort study among 32 757 cancer survivors

Abstract: We examined the incidence of cardiovascular disease (CVD) among 32 757 cancer survivors and age‐, gender‐, and geographically matched cancer‐free controls during a follow‐up period of 1‐13 years, and explored whetherCVD incidence differed by received cancer treatment, traditional cardiovascular risk factors, age, or gender. Adult 1‐year cancer survivors without a history ofCVD diagnosed with breast (n = 6762), prostate (n = 4504), non‐Hodgkin (n = 1553), Hodgkin (n = 173), lung and trachea (n = 2661), basal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 29 publications
3
54
1
Order By: Relevance
“…Hence, these men had a relatively lower a priori risk for developing CVD, which means there was room for the increased risk of developing CVD by being pharmaceutically treated for depression. As previously demonstrated in this patient sample, there is an increased risk of receiving hormone treatment for incident CVD . The present results show that there might be an additive effect, as pharmaceutically treated depression increases the risk of CVD only amongst men who are treated with hormones.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Hence, these men had a relatively lower a priori risk for developing CVD, which means there was room for the increased risk of developing CVD by being pharmaceutically treated for depression. As previously demonstrated in this patient sample, there is an increased risk of receiving hormone treatment for incident CVD . The present results show that there might be an additive effect, as pharmaceutically treated depression increases the risk of CVD only amongst men who are treated with hormones.…”
Section: Discussionsupporting
confidence: 83%
“…First, traditional CVD risk factors such as hypertension, hypercholesterolaemia, and diabetes mellitus, are known to play an important role in the pathogenesis of CVD . The involvement of these risk factors has been confirmed to play a role in incident CVD among various malignancies as well . More recently, several studies have shown that psychological distress, such as being anxious or depressed, also increases the risk of the development and progression of CVD among non‐cancer populations, independent of traditional biomedical risk factors .…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…1 Fox Chase Cancer Center; 2 Yale Cancer Center/Smilow Cancer Hospital; 3 Vanderbilt-Ingram Cancer Center; 4 University of Colorado Cancer Center; 5 City of Hope National Medical Center; 6 Fred Hutchinson Cancer Research Center/Seattle Cancer Care Alliance; 7 Mayo Clinic Cancer Center; 8 O'Neal Comprehensive Cancer Center at UAB; 9 UCSF Helen Diller Family Comprehensive Cancer Center; 10 University of Michigan Rogel Cancer Center; 11 Abramson Cancer Center at the University of Pennsylvania; 12 St. Jude Children's Research Hospital/The University of Tennessee Health Science Center; 13 Moffitt Cancer Center; 14 UC San Diego Moores Cancer Center; 15 Massachusetts General Hospital Cancer Center; 16 Huntsman Cancer Institute at the University of Utah; 17 Case Comprehensive Cancer Center/University Hospitals Seidman Cancer Center and Cleveland Clinic Taussig Cancer Institute; 18 Memorial Sloan Kettering Cancer Center; 19 Roswell Park Comprehensive Cancer Center; 20 The Ohio State University Comprehensive Cancer Center -James Cancer Hospital and Solove Research Institute; 21 Siteman Cancer Center at Barnes-Jewish Hospital and Washington University School of Medicine; 22 Dana-Farber/Brigham and Women's Cancer Center; 23 The University of Texas MD Anderson Cancer Center; 24 The Sidney Kimmel Comprehensive Cancer Center at Johns Hopkins; 25 Duke Cancer Institute; 26 University of Wisconsin Carbone Cancer Center; 27…”
Section: Please Notementioning
confidence: 99%